Changes in soil microbial community structure during the transformation from native soil to alfalfa cultivation soil in the Kunlun Mountain sand area, Xinjiang, China - Chen, Yongcheng; Li, Xiao; Huang, Rongzheng; Zhang, Fanfan; Ma, Chunhui (Frontiers in Microbiology, 2025)
Alfalfa cultivation is widely regarded as an effective biological approach for improving desertified and degraded soils. However, it remains unclear how this effect unfolds in high-altitude desert environments and how soil and plant microbiomes assemble when native soil (NS) host plants are replaced. In this study, we tested whether converting NS to alfalfa-cultivated soil (CS) affected the composition of soil microbial communities and changed microbial diversity. Specifically, alfalfa cultivation reshaped core microbial components, increasing beneficial bacteria such as Arthrobacter and Pseudomonas, potentially enhancing nutrient cycling and plant growth, while reducing certain decomposers (e.g., Bacteroides). Results indicated that alfalfa cultivation improved NS quality, and with longer planting time, promoted the recovery and homogenization of soil microbial diversity. This process was accompanied by the replenishment or exclusion of soil microorganisms. Soil organic matter and pH were identified as key drivers of microbial community change. Across 541 bacterial OTUs and 56 fungal OTUs were shared across NS, CS, and alfalfa rhizosphere soil (RS), this core microbiome accounted for a large proportion of reads (bacteria: 28.70%, fungi: 40.37%). Microbial network structure and interactions were more complex NS and RS than in CS, with bacterial interactions more pronounced than fungal ones. Overall, the transition from NS to CS via alfalfa planting positively affected local microbial diversity, and RS assembly was shaped by both recruitment and dispersal. This research highlights the potential of alfalfa to restore high-altitude desertified ecosystems by strengthening microbially mediated soil fertility and biogeochemical cycling, offering insights for sustainable land management in arid regions.